2021
DOI: 10.1101/2020.12.26.20248491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A trans-ancestry genome-wide association study of unexplained chronic ALT elevation as a proxy for nonalcoholic fatty liver disease with histological and radiological validation

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a prevalent, heritable trait that can progress to cancer and liver failure. Using our recently developed proxy definition for NAFLD based on chronic liver enzyme elevation without other causes of liver disease or alcohol misuse, we performed a multi-ancestry genome-wide association study in the Million Veteran Program with 90,408 NAFLD cases and 128,187 controls. Seventy-seven loci exceeded genome-wide significance of which 70 were novel, with an additional European-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 189 publications
2
22
2
Order By: Relevance
“…Our approach also points at novel, shared genetic architecture of traits. For example, two genes previously associated with non-alcoholic fatty liver disease, or NAFLD (COBLL1 and PNPLA3) [40,41], show colocalization in liver (Fig. 6), the former with fasting insulin and BMI and the latter with T2D, HDL, and TG, implicating them as shared genetic associations for IR/T2D and NAFLD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our approach also points at novel, shared genetic architecture of traits. For example, two genes previously associated with non-alcoholic fatty liver disease, or NAFLD (COBLL1 and PNPLA3) [40,41], show colocalization in liver (Fig. 6), the former with fasting insulin and BMI and the latter with T2D, HDL, and TG, implicating them as shared genetic associations for IR/T2D and NAFLD.…”
Section: Discussionmentioning
confidence: 89%
“…For 30 of our candidate causal genes, we observed a response to atorvastatin, metformin, or rosiglitazone, three drugs used for the treatment of cardiometabolic diseases. For instance, COBLL1, a gene with liverspecific colocalization for fasting insulin and BMI and previously associated with non-alcoholic fatty liver disease [40,41], showed decreased expression under both atorvastatin and metformin in liver. Another gene, GPAM, which colocalized with HDL and TG also in liver, showed reduced expression under all three of these treatments (atorvastatin and metformin in liver, rosiglitazone in fat cells).…”
Section: Perturbation With Physiological and Pharmacological Regulators Contextualizes Candidate Causal Genesmentioning
confidence: 99%
“…The range of Mendelian ABCB4 associated phenotypes has been noted to follow both autosomal dominant and recessive modes of inheritance. Furthermore, in large-scale population-based studies, variation in ABCB4 has been statistically associated with elevated risk for a number of liver-related phenotypes, including risk for non-alcoholic fatty liver disease[45], elevated serum liver enzyme levels[46,47], and risk for hepatobiliary carcinoma[48], suggesting that common variation in this gene may play a broader role in liver disease risk in the human population.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic lipid accumulation is highly associated with IR (50) and, for this reason, a number of candidate gene analyses have focused on hepatic lipid metabolism genes, particularly on those pinpointed by genetic association studies. A number of GWAS have implicated FADS2 in IR-related diseases (51)(52)(53). FADS2 (delta-6 desaturase) is a rate-limiting enzyme in long-chain polyunsaturated fatty acids Comparison of obese T2D and non-T2D revealed that the IRS2 locus, which encodes a core mediator of insulin signalling in the liver, is differentially methylated in the livers of T2D patients (41).…”
Section: Fads2mentioning
confidence: 99%